A study of the mango market in the European Union - Araújo, José Lincoln Pinheiro; Garcia, José Luis Lopez (Revista Econômica do Nordeste, 2016)
This study describes the mango market in the European Union, the largest importer of Brazilian mangos. For such, we find support in the in-depth interview method for obtaining information from importers, wholesalers and supervisors of horticultural sectors of supermarkets and fruit shops in Spain as well as import agents from other EU countries. The results showed an upward trend for mango consumption in the European Union. With regard to the market behavior of the main mango varieties, we realized that Tommy Atkins mango is classified in two stages of sales lifecycle: maturity and decline; Kent mango is found to be ascending in the maturity stage; Haden and Keitt mango are stabilized in the maturity stage, whilst Palmer, Maya and Shelly mango are classified in the growth stage. The study also showed four well-defined segments in the EU fresh mango market: 1) consumers who priorize the relationship between quality and competitive prices; 2) ‘premium-product’ consumers; 3) organic product consumers; and 4) consumers of the pre-peeled, readyto- eat product.